Self-efficacy as a predictor of mental readiness during the pre-embarkation transition among Indonesian maritime cadets - Inayatur Robbany; Niken Sitalaksmi Widjaja; Hafis Aulia; Aliya Izet Begovic Yahya (Jurnal Konseling dan Pendidikan, 2026)
The pre-embarkation period before the first sea practical training is a psychologically demanding transition in maritime education, yet limited evidence has identified the psychological resources that best explain cadets' readiness for this phase. This study examined self-efficacy as a predictor of mental readiness among Indonesian maritime cadets. A quantitative cross-sectional predictive validity design was conducted with 178 Diploma IV cadets from the Nautical and Engineering departments of STIP Jakarta, selected through proportionate stratified random sampling. The Self-Efficacy Scale and Mental Readiness Inventory demonstrated strong reliability (Cronbach's α = .89 and .91, respectively). Self-efficacy was positively associated with mental readiness (r = .67, p < .001) and significantly predicted mental readiness (β = .67, B = 0.75, p < .001), explaining 45.1% of the variance (R² = .451). Nautical cadets reported significantly higher mental readiness than Engineering cadets (M = 3.95 vs. 3.53; Cohen's d = 0.78), while self-efficacy remained a significant predictor after controlling for gender and prior ship-visit experience, both of which were non-significant. These findings indicate that higher self-efficacy is consistently associated with greater mental readiness during the pre-embarkation transition, although the cross-sectional design does not support causal inference. The study highlights the value of integrating self-efficacy-enhancing strategies, such as simulation-based mastery experiences and structured mentoring, into maritime education to strengthen cadets' psychological preparedness. Longitudinal and multi-institutional research is recommended to verify the stability and generalizability of these findings.